PROSPECTS OF DIGITALIZATION IN THE FIELD OF OCCUPATIONAL HEALTH AND SAFETY: Array - Krainiuk, O.; Buts, Yu.; Barbachin, V.; Didenko, N. (Municipal economy of cities. Series: «Economy science», 2020)
The modern world is impossible to imagine without digital technologies that are implemented in all areas of activity, including helping to address occupational safety. The purpose of this work was to consider the prospects and problems of implementation of information technology in the field of occupational safety, as well as ways to improve the use of digital technologies by health and safety professionals for more effective risk management and safety. Digitalization (digitalization) in labor protection is a transformation of OSH, which involves the use of digital technologies to optimize management, increase company productivity and improve working conditions and reduce the number of occupational diseases and accidents. The main procedures of digitalization, which are implemented in the field of labor protection, are highlighted. The main components of successful implementation of digital solutions in occupational safety are highlighted. The conditions for the introduction of digitalization in the management system of labor protection are formed. Various innovations, from process automation to the proliferation of field sensors and the transition to predictive analytics, will allow employees and organizations to make significant improvements in health and safety if they are able to take advantage of the opportunities that open up. In the coming years, there will be a shift from passive monitoring to specific recommendations that will give people software applications. Gadget data collected by gadgets will be used to assess occupational risk and occupational disease insurance. There are already examples of testing these technologies to increase productivity and reduce employee injuries. The considered technologies do not appear and are not used alone, the interconnected and complex, system approach is usually observed. Thus, all the tools listed in the introduction of digital technologies in the modernization of occupational safety management contribute to reducing the number of accidents.